Measuring Rural P-12 Teachers’ Attitudes, Perceptions, and Utilizations of Social Media - Stewart Waters; Matt Hensley (Research in Social Sciences and Technology, 2020)
Social media continues to evolve and change the way people interact, learn, and communicate. As social media continues to grow in importance within societies, it is critical to better understand how teachers view social media as an educational resource. This quantitative study examines the general attitudes, perceptions, and utilizations of social media among P-12 teachers in a rural school district. Findings indicate that most teachers view social media as a high risk proposition for student use in the classroom, but do see social media as potentially useful and relevant to learning in the P-12 classroom.